PRL w narracji muzealnej 1989-2017 - Wąchała-Skindzier, Maria (2023)
THE POLISH PEOPLE’S REPUBLIC IN THE MUSEUM NARRATIVE OF 1989–2017The main goal of this dissertation is to analyse the representation of the Polish People’s Republic in the museum narrative. The dissertation is written from a narrative perspective and from the point of view of new museology with the help of research categories such as the narrative museum, communicative, cultural, and collective memory, historical representation, heritage, historical policy, etc. The research method is twofold. First, a quantitative analysis is performed of statistical data, i.e. a list of temporary and permanent exhibitions devoted to the Polish People’s Republic and displayed in Polish museums between 1989 and 2017. The list was compiled on the basis of queries sent out to the Polish museums featured in the database of the National Institute for Museums and Public Collections and was verified by the author.